Neuroanatomical correlates of reality monitoring in patients with schizophrenia and auditory hallucinations. Issue 1 (22nd September 2021) - Perret, Mélanie; Lavallé, Layla; Haesebaert, Frédéric; Suaud-Chagny, Marie-Françoise; Brunelin, Jérôme; Mondino, Marine
Abstract: Background: Reality-monitoring process enables to discriminate memories of internally generated information from memories of externally derived information. Studies have reported impaired reality-monitoring abilities in schizophrenia patients with auditory hallucinations (AHs), specifically with an exacerbated externalization bias, as well as alterations in neural activity within frontotemporoparietal areas. In healthy subjects, impaired reality-monitoring abilities have been associated with reduction of the paracingulate sulcus (PCS). The current study aimed to identify neuroanatomical correlates of reality monitoring in patients with schizophrenia. Methods: Thirty-five patients with schizophrenia and AHs underwent a reality-monitoring task and a 3D anatomical MRI scan at 1.5 T. PCS lengths were measured separately for each hemisphere, and whole-brain voxel-based morphometry analyses were performed using the Computational Anatomy Toolbox (version 12.6) to evaluate the gray-matter volume (GMV). Partial correlation analyses were used to investigate the relationship between reality-monitoring and neuroanatomical outcomes (PCS length and GMV), with age and intracranial volume as covariates. Results: The right PCS length was positively correlated with reality-monitoring accuracy (Spearman's ρ  = 0.431, p  = 0.012) and negatively with the externalization bias (Spearman's ρ  = −0.379, p  = 0.029). Reality-monitoring accuracy was positively correlated with GMV in the right angular gyrus, whereas externalization bias was negatively correlated with GMV in the left supramarginal gyrus/superior temporal gyrus, in the right lingual gyrus and in the bilateral inferior temporal/fusiform gyri (voxel-level p  < 0.001 and cluster-level p  < 0.05, FDR-corrected). Conclusions: Reduced reality-monitoring abilities were significantly associated with shorter right PCS and reduced GMV in temporal and parietal regions of the reality-monitoring network in schizophrenia patients with AHs.